Mechanism of Human Plasminogen Activation by Streptokinase and Human Plasmin - Blatt, W. F; Gray, JL; Jensen, H (Thrombosis and Haemostasis, 1964)
A sensitive tool has been described for measuring fibrinolysis in reconstituted systems using thrombelastography. Activator mixtures with no appreciable proteolytic activity can similarly be tested in this system when the fibrinogen utilized has sufficient plasminogen present. Exposure of human plasminstreptokinase mixtures formed at pH 7.0 to acid conditions produced a striking loss of activator activity which could not be ascribed to low pH lability of the components, nor to plasmin action on the SK at pH 2.0. This is additional evidence for the hypothesis that human plasmin interacts with SK to form a complex capable of converting human and bovine plasminogen to plasmin.